The Impact of Releasing Domestic Dogs on the Spread of Rabies Disease and Its Prevention - Ahmad Fitri, Afit; Marsudi, Marsudi; Trisilowati, Trisilowati (The Journal of Experimental Life Science, 2023)
The government's program to achieve rabies-free status by 2030 is an initiative to accelerate the eradication of rabies cases in Indonesia. Rabies is a highly contagious disease with a 100% fatality rate, and dogs are the main carriers of the virus. The government's efforts to minimize rabies cases include vaccination of susceptible animals, eliminating rabid dogs, and implementing dog population management (MPA). Field observations indicate that the practice of releasing domestic dogs allowing them to roam freely, has led to an increase in rabies cases. Using mathematical modeling, this husbandry system's impact can be simulated. Based on the model analysis, it is determined that a maximum of 15% of domestic dogs should be allowed to roam freely. If this threshold is exceeded, it becomes necessary to ensure a minimum of 20% vaccination coverage and eliminate at least 1% of rabid dogs. Keywords: Dogs, Rabies Disease, Releasing Domestic Dogs.